Pricing Mechanism and IPO Initial Return: Evidence from Pakistan Stock Exchange - Waqas Mehmood; Rasidah Mohd-Rashid; Abd Halim Ahmad (International Journal of Business and Society, 2020)
This study adds to the extent of the literature by examining the impacts of pricing mechanism and premium offered on IPO initial return in Pakistan. Cross-sectional data were gathered using 90 listed IPOs retrieved from Pakistan stock exchange. Accordingly, ordinary least squares, quantile regression, robustness regression, and stepwise regression were employed to assess the factors that influenced initial return. This study describes the intensity of initial return in light of company specific and issue specific variables. Both closing and opening prices to offer price were incorporated to measure the initial return on the initial day of trading. The outcomes showed that after the reform of book building pricing mechanism, the initial return of IPOs increased, when compared to the fixed price offerings in Pakistan. This study concludes that information from book building pricing mechanism and premium had influenced both issuer and investor in subscribing IPO.